THE ROLE OF FINANCIAL INSTITUTIONS AND SOCIAL SECURITY FOR INDONESIAN HOUSEHOLD OPPORTUNITIES TO OPENS BUSINESSES - Cahyono, Eko Fajar (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2020)
The purpose of this study was to test Fahim Khan's model. The model states that the existence of government assistance and social security will increase one's chances of becoming entrepreneurs. The model has the argument that government assistance and social security will provide better risk protection for entrepreneurs. By analyzing more than 15.000 sample data from the Indonesian Family Life Survey, this study examines the proposed Fahim Khan model that Islamic economics encourages entrepreneurship with two important factors, financial and funding social security institutions. The results of this study are obtained from the logistic regression method stating that there are influences of social security and financial institution financing on the opportunity to open a business. Furthermore, this study produced several important findings, such as bank loans and social security have an impact to the opportunity for Indonesian household of opening a business. Either partially or simultaneously all independent variables (bank loans, pension security, insurance claims, national healthcare security membership, national accident care security membership, national pension care membership, national death care security membership) have a significant effect on the business. The results show that there are three variables that have a negative relationship with business, namely the national healthcare security membership variable, the national accident care security membership variable and the national pension care security membership variable.